BISAKAH PENGETAHUAN AUDITOR DAN SPIRITUAL CAPITAL DIGUNAKAN UNTUK MENGATASI DILUTION EFFECT PADA AUDIT JUDGMENT? - Pertiwi, I Dewa Ayu Eka; Munidewi, Ida Ayu Budhananda; Pradipa, Nyoman Angga (Media Akuntansi dan Perpajakan Indonesia, 2022)
The dilution effect indicates the use of inappropriate information to make predictions, where diagnostic information is diluted by non-diagnostic information. Under the influence of non-diagnostic information, human predictions are not correct. Auditor knowledge is the auditor's understanding of the level of a job, both conceptually and theoretically. The negative impact of the dilution effect can affect audit quality, which can affect the auditor's ability to categorize some information based on its relevance during the process. The purpose of this study was to examine whether the dilution effect and auditor knowledge gained from training and work experience, and spiritual capital affect audit considerations in determining fraud risk. In an organized situation, this study was conducted using vignette and ANOVA to test the three hypotheses and simple regression to test the fourth hypothesis. The subjects of this research are auditors from Public Accounting Firms, especially in Bali and Nusa Tenggara. There are several findings that can be expected in this study. First, the dilution effect has an adverse impact on the auditor's mind when making judgments during a fraud risk assessment. Auditors who are not exposed to the dilution effect will provide a more accurate assessment than auditors who are exposed to the dilution effect. Second, auditor knowledge has a significant effect on audit considerations in detecting fraud. Auditors who have higher knowledge will make more accurate assessments than auditors who have lower knowledge. The third finding is that auditors can be better at making audit judgments to assess the risk of fraud if they are equipped with spiritual capital. The fourth finding, however, shows that auditors who have higher knowledge and spiritual capital will still make inappropriate judgments during fraud risk assessments when they are exposed to the dilution effect.